Morphology of generative bodies of the introduced apricots in Mangistau’s arid conditions - Иманбаева, А.А.; Косарева, О.Н.; Динова, Г.; Ахтанова, А. (Fundamental and Experimental Biology, 2015)
40 years’ experience of an introduction at the territory of Mangyshlak revealed availability of cultivation of apricot ordinary in local conditions. Morphological studying and the description of the introduced breeds of apricot ordinary allowed to reveal a big variety of morphology of generative bodies at grades of the Kazakhstan selection, and at the same time their most the general morphological features.